Anticoagulation in COVID-19: Effect of Enoxaparin, Heparin, and Apixaban on Mortality - Billett, Henny H.; Reyes-Gil, Morayma; Szymanski, James; Ikemura, Kenji; Stahl, Lindsay R.; Lo, Yungtai; Rahman, Shafia; Gonzalez-Lugo, Jesus D.; Kushnir, Margarita; Barouqa, Mohammad; Golestaneh, Ladan; Bellin, Eran (Thrombosis and Haemostasis, 2020)
Background Mortality in coronavirus disease of 2019 (COVID-19) is associated with increases in prothrombotic parameters, particularly D-dimer levels. Anticoagulation has been proposed as therapy to decrease mortality, often adjusted for illness severity.Objective We wanted to investigate whether anticoagulation improves survival in COVID-19 and if this improvement in survival is associated with disease severity.Methods This is a cohort study simulating an intention-to-treat clinical trial, by analyzing the effect on mortality of anticoagulation therapy chosen in the first 48 hours of hospitalization. We analyzed 3,625 COVID-19+ inpatients, controlling for age, gender, glomerular filtration rate, oxygen saturation, ventilation requirement, intensive care unit admission, and time period, all determined during the first 48 hours.Results Adjusted logistic regression analyses demonstrated a significant decrease in mortality with prophylactic use of apixaban (odds ratio [OR] 0.46, p = 0.001) and enoxaparin (OR = 0.49, p = 0.001). Therapeutic apixaban was also associated with decreased mortality (OR 0.57, p = 0.006) but was not more beneficial than prophylactic use when analyzed over the entire cohort or within D-dimer stratified categories. Higher D-dimer levels were associated with increased mortality (p < 0.0001). When adjusted for these same comorbidities within D-dimer strata, patients with D-dimer levels < 1 µg/mL did not appear to benefit from anticoagulation while patients with D-dimer levels > 10 µg/mL derived the most benefit. There was no increase in transfusion requirement with any of the anticoagulants used.Conclusion We conclude that COVID-19+ patients with moderate or severe illness benefit from anticoagulation and that apixaban has similar efficacy to enoxaparin in decreasing mortality in this disease.
Keywords: anticoagulation; apixaban; COVID-19; D-dimer; enoxaparin; mortality